Valdivia’s turrets: Vestiges of the walled city - Liewald-Dessy, Lorena (2019)
Valdivia City suffered a transformation after its refoundation in 1647 as a walled city. During the XVII and the XVIII century a process of consecutive improvement for the walls or fences was pursuit. All this was a product of the climatic and geographic situations, as well as military engineering requirements. In this process two Turrets were built by the same quarter of the XVIII. Its origin was justified by the need of strengthening two points considered as strategic and vulnerable in the city. Moreover, population protection was not the only purpose, but also to consolidate the progress to other zones, which by that time were under mapuche-huilliche domain. During the second decade of the XX, both turrets were declared as Historical Monument. These are two postcards which identify the city, but they lack the meaning and sense by which they were built.